Natural resource abundance and broad-based financial development nexus in ASEAN countries: Accounting for globalization and human capital - Solomon Prince Nathaniel (European Journal of Government and Economics (EJGE), 2021)
Sustainable resource consumption is important for the development of the financial system. Besides, an advanced financial system eases the transfer of revenues from production activities and export to productive investments. The influence of natural resource (NR) abundance on financial development (FD) is still an ongoing debate with conflicting results. However, this study applies a novel proxy for FD, which measures the efficiency, accessibility, and depth of the financial market and institutions. Therefore, the current study is a maiden attempt to explore the nexus between FD and NR abundance amidst globalization, human capital, and economic growth in ASEAN economies. Reliable panel econometric techniques, including second-generation unit root tests, Westerlund (2007) cointegration tests, and the Augmented Mean Group (AMG) estimator are employed on the data for the period 1990-2017. The preliminary tests affirm the existence of cross-sectional dependence, unit root, and cointegrating relationship among the variables. The findings from the study reveal that NR abundance reduces FD, while globalization, human capital and economic growth add to FD. A feedback causality exists between NR abundance and FD. Thus, this study argues that more investment in the manufacturing sector will ease the attainment of efficiency in financial sector accessibility and benefits from NR abundance.
Keywords: E44; N57; P48; Q32; Q33; 330; natural resource abundance; globalization; financial development; human capital; ASEAN; AMG